New Role for Interleukin‐13 Receptor α1 in Myocardial Homeostasis and Heart Failure. Issue 5 (May 2017) - Amit, Uri; Kain, David; Wagner, Allon; Sahu, Avinash; Nevo‐Caspi, Yael; Gonen, Nir; Molotski, Natali; Konfino, Tal; Landa, Natalie; Naftali‐Shani, Nili; Blum, Galia; Merquiol, Emmanuelle; et al.
Abstract : Background: The immune system plays a pivotal role in myocardial homeostasis and response to injury. Interleukins‐4 and ‐13 are anti‐inflammatory type‐2 cytokines, signaling via the common interleukin‐13 receptor α1 chain and the type‐2 interleukin‐4 receptor. The role of interleukin‐13 receptor α1 in the heart is unknown. Methods and Results: We analyzed myocardial samples from human donors (n=136) and patients with end‐stage heart failure (n=177). We found that the interleukin‐13 receptor α1 is present in the myocardium and, together with the complementary type‐2 interleukin‐4 receptor chain Il4ra, is significantly downregulated in the hearts of patients with heart failure. Next, we showed that Il13ra1 ‐deficient mice develop severe myocardial dysfunction and dyssynchrony compared to wild‐type mice (left ventricular ejection fraction 29.7±9.9 versus 45.0±8.0; P =0.004, left ventricular end‐diastolic diameter 4.2±0.2 versus 3.92±0.3; P =0.03). A bioinformatic analysis of mouse hearts indicated that interleukin‐13 receptor α1 regulates critical pathways in the heart other than the immune system, such as extracellular matrix (normalized enrichment score=1.90; false discovery rate q=0.005) and glucose metabolism (normalized enrichment score=−2.36; false discovery rate q=0). Deficiency of Il13ra1 was associated with reduced collagen deposition under normal and pressure‐overload conditions. Conclusions: The results of our studies in humans and mice indicate, for the first time, a role of interleukin‐13 receptor α1 in myocardial homeostasis and heart failure and suggests a new therapeutic target to treat heart disease.